A specialization inequality for tropical complexes. (30th April 2021) - Cartwright, Dustin
Abstract : We prove a specialization inequality relating the dimension of the complete linear series on a variety to the tropical complex of a regular semistable degeneration. Our result extends Baker's specialization inequality to arbitrary dimension.